Teachers’ Attributes for Professional Development - Pandey, Shiv Ram (Madhyabindu Journal, 2023)
The main purpose of this paper is to explore the traits of professional teachers in general and English teachers in particular. To accomplish the purpose, the principal research question for this study is: What qualities make English teachers professionals? Therefore, this paper presents the qualities of professional English language teachers. For this, qualitative method has been adopted. Purposive sampling was chosen to get in-depth information. An unstructured interview technique was adopted to collect data with five English teachers The analytical approach I have used is inductive. The article focuses attention on the attributes of teachers which play a pivotal role in making them professionals in teaching and learning process. The professionals are ones who not only have the academic degree but also have training, knowledge of the contents, competence and confidence in performing the job. They are critical and creative. They present and publish, and love learners, community of practice and profession.